Increased Expression of PDK4 Was Displayed in Gastric Cancer and Exhibited an Association With Glucose Metabolism - Liu, Bin; Zhang, Yang; Suo, Jian (Frontiers in Genetics, 2021)
Previous studies reported that Pyruvate dehydrogenase kinase 4 (PDK4) is closely related to diabetes, heart disease and carcinomas. Nevertheless, the role of PDK4 in gastric cancer (GC) occurrence and development is yet poorly understood. Our experiments were taken to evaluate PDK4’s function in GC. The TCGA tumor genome map database was employed to validate the levels of PDK family in different grades and stages of GC. The survival ratio of PDK families in GC was detected by The Kaplan-Meier plotter database. The links existing in the expression of PDK family and the level of tumor infiltrating immune cells was investigated by tumor immunity assessment resource (TIMER). PDK4-associated signal pathways in GC were analyzed by The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. PDK4 mRNA level in the GC cells was measured by qRT-PCR. Cell counting kit-8 (CCK-8) and Transwell assays were separately carried out to evaluate PDK4-induced influence on GC cell proliferation, migration and invasion. Our data suggested that GC cells highly expressed PDK4, and PDK4 expression presented significant relation with the staging, grade and survival rate of GC. PDK4 expression presented positive correlation with the types of different infiltrating immune cells, comprising B cells, CD4+ T cells and dendritic cells. Meanwhile, PDK4 expression exhibited strong association with macrophages. Survival analysis revealed that the expression of PDK4 displayed a relationship with the prognosis of patients. Therefore, PDK4 was liable to be a biomarker for prognosis. Our results further displayed that PDK4 might modulate glycolysis’s level in GC cells and its expression was associated with GC cell proliferation, migration and invasion. These data may provide insights into designing a new treatment strategy for GC.